Marketing Mix Kantin Parklatz Unit Usaha Universitas Darussalam Gontor dalam Meningkatkan Minat Konsumen (Ditinjau dari Perspektif Islam) - Imam Haryadi; Fajar Shodiq (Universitas Darussalam Gontor, 2021)
The marketing mix will be the basis for every business actor to maintain the success of the business. The main problem in this research is the application of the marketing mix of the Parklatz Canteen in increasing consumer interest at the University of Darussalam Gontor based on an Islamic perspective. So in this study aims to determine the application of the marketing mix of Kantin Parklatz in increasing consumer interest at the University of Darussalam Gontor based on an Islamic perspective. In this study, researchers used a qualitative descriptive study, the data collection techniques used were observation, interviews, and documentation. Meanwhile, data analysis used data analysis model of Miles and Huberman which includes three steps, namely data reduction, data presentation, and drawing conclusions. The results of this research, that in the application of the marketing mix of Kantin Parklatz is quite effective in increasing consumer interest. Therefore, all the existing marketing mix variables have been implemented well. However, overall the application of the marketing mix has not applied it. So that in the end it affects the marketing mix related to prices and promotions, namely that there are still unsatisfactory services such as during the payment process.